Bioaccumulation kinetics and toxic effects of Cr, Ni and Zn on Eichhornia crassipes - Hadad, Hernán Ricardo (2011)
The aim of this work was to assess the uptake efficiencies, the uptake and bioaccumulation kinetics and the toxic effects of Cr, Ni and Zn on Eichhornia crassipes. Plants were exposed to 1mg L−1 of each metal and sampled during 30 days. E. crassipes removed 81%, 95% and 70% of Cr, Ni and Zn, respectively. Metal removal from water involved a fast and a slow component. Metals were accumulated fundamentally by roots. Cr was scarcely translocated to aerial parts. In these tissues, Ni showed the highest accumulation amount while Zn presented the highest accumulation rate. Metal toxicity on the biomass was different among treatments. However, biomass did not decrease in any case. All the studied metals produced chlorophyll decrease. The root cross-sectional area (CSA) and vessel number increased and the root length decreased when plants were exposed to Zn. Despite the toxic effects, E. crassipes accumulated Cr, Ni and Zn efficiently. Zn efficiently. removal from water involved a fast and a slow component. Metals were accumulated fundamentally by roots. Cr was scarcely translocated to aerial parts. In these tissues, Ni showed the highest accumulation amount while Zn presented the highest accumulation rate. Metal toxicity on the biomass was different among treatments. However, biomass did not decrease in any case. All the studied metals produced chlorophyll decrease. The root cross-sectional area (CSA) and vessel number increased and the root length decreased when plants were exposed to Zn. Despite the toxic effects, E. crassipes accumulated Cr, Ni and Zn efficiently. Zn efficiently. and sampled during 30 days. E. crassipes removed 81%, 95% and 70% of Cr, Ni and Zn, respectively. Metal removal from water involved a fast and a slow component. Metals were accumulated fundamentally by roots. Cr was scarcely translocated to aerial parts. In these tissues, Ni showed the highest accumulation amount while Zn presented the highest accumulation rate. Metal toxicity on the biomass was different among treatments. However, biomass did not decrease in any case. All the studied metals produced chlorophyll decrease. The root cross-sectional area (CSA) and vessel number increased and the root length decreased when plants were exposed to Zn. Despite the toxic effects, E. crassipes accumulated Cr, Ni and Zn efficiently. Zn efficiently. removal from water involved a fast and a slow component. Metals were accumulated fundamentally by roots. Cr was scarcely translocated to aerial parts. In these tissues, Ni showed the highest accumulation amount while Zn presented the highest accumulation rate. Metal toxicity on the biomass was different among treatments. However, biomass did not decrease in any case. All the studied metals produced chlorophyll decrease. The root cross-sectional area (CSA) and vessel number increased and the root length decreased when plants were exposed to Zn. Despite the toxic effects, E. crassipes accumulated Cr, Ni and Zn efficiently. Zn efficiently. Eichhornia crassipes. Plants were exposed to 1mg L−1 of each metal and sampled during 30 days. E. crassipes removed 81%, 95% and 70% of Cr, Ni and Zn, respectively. Metal removal from water involved a fast and a slow component. Metals were accumulated fundamentally by roots. Cr was scarcely translocated to aerial parts. In these tissues, Ni showed the highest accumulation amount while Zn presented the highest accumulation rate. Metal toxicity on the biomass was different among treatments. However, biomass did not decrease in any case. All the studied metals produced chlorophyll decrease. The root cross-sectional area (CSA) and vessel number increased and the root length decreased when plants were exposed to Zn. Despite the toxic effects, E. crassipes accumulated Cr, Ni and Zn efficiently. Zn efficiently. removal from water involved a fast and a slow component. Metals were accumulated fundamentally by roots. Cr was scarcely translocated to aerial parts. In these tissues, Ni showed the highest accumulation amount while Zn presented the highest accumulation rate. Metal toxicity on the biomass was different among treatments. However, biomass did not decrease in any case. All the studied metals produced chlorophyll decrease. The root cross-sectional area (CSA) and vessel number increased and the root length decreased when plants were exposed to Zn. Despite the toxic effects, E. crassipes accumulated Cr, Ni and Zn efficiently. Zn efficiently. E. crassipes removed 81%, 95% and 70% of Cr, Ni and Zn, respectively. Metal removal from water involved a fast and a slow component. Metals were accumulated fundamentally by roots. Cr was scarcely translocated to aerial parts. In these tissues, Ni showed the highest accumulation amount while Zn presented the highest accumulation rate. Metal toxicity on the biomass was different among treatments. However, biomass did not decrease in any case. All the studied metals produced chlorophyll decrease. The root cross-sectional area (CSA) and vessel number increased and the root length decreased when plants were exposed to Zn. Despite the toxic effects, E. crassipes accumulated Cr, Ni and Zn efficiently. Zn efficiently. E. crassipes accumulated Cr, Ni and Zn efficiently.